Delivering interventions for depression by using the internet: randomised controlled trial. Issue 7434 (23rd January 2004) - Christensen, Helen; Griffiths, Kathleen M; Jorm, Anthony F
Abstract: Objective To evaluate the efficacy of two internet interventions for community-dwelling individuals with symptoms of depression—a psychoeducation website offering information about depression and an interactive website offering cognitive behaviour therapy. Design Randomised controlled trial. Setting Internet users in the community, in Canberra, Australia. Participants 525 individuals with increased depressive symptoms recruited by survey and randomly allocated to a website offering information about depression (n = 166) or a cognitive behaviour therapy website (n = 182), or a control intervention using an attention placebo (n = 178). Main outcome measures Change in depression, dysfunctional thoughts; knowledge of medical, psychological, and lifestyle treatments; and knowledge of cognitive behaviour therapy. Results Intention to treat analyses indicated that information about depression and interventions that used cognitive behaviour therapy and were delivered via the internet were more effective than a credible control intervention in reducing symptoms of depression in a community sample. For the intervention that delivered cognitive behaviour therapy the reduction in score on the depression scale of the Center for Epidemiologic Studies was 3.2 (95% confidence interval 0.9 to 5.4). For the "depression literacy" site (BluePages), the reduction was 3.0 (95% confidence interval 0.6 to 5.2). Cognitive behaviour therapy (MoodGYM) reduced dysfunctional thinking and increased knowledge of cognitive behaviour therapy. Depression literacy (BluePages) significantly improved participants' understanding of effective evidence based treatments for depression (P < 0.05). Conclusions Both cognitive behaviour therapy and psychoeducation delivered via the internet are effective in reducing symptoms of depression.